The autonomy-enhancing effects of choice on cognitive load, motivation and learning with digital media. (December 2018) - Schneider, Sascha; Nebel, Steve; Beege, Maik; Rey, Günter Daniel
Abstract: According to the Self-Determination Theory, the autonomy-supporting feature of choice leads to an increase in intrinsically motivated behavior. Although this effect was replicated multiple times, instructional designers often dread to include choice options in single tasks because of the high effort in designing additional materials or a higher cognitive load for students. This study used a feigned choice paradigm to avoid additional efforts for designers. Moreover, this study examined the mediational influences of learners' perceived autonomy and intrinsic motivation on choice effects and the moderating influence of the relevance of choice options . In Experiment 1, 79 secondary school students were randomly assigned to either a group with a feigned topic choice or a group without the possibility to choose. Results show that both retention and transfer performance (learning scores) were enhanced by choice options. In addition, the effect of choice on retention was mediated by perceived autonomy but not by intrinsic motivation. In Experiment 2, 87 secondary school students were assigned to a 2 (with or without a feigned learning-relevant choice) x 2 (with or without a feigned learning-irrelevant choice) design in order to additionally examine the moderating effects of relevance of choice options. All results of Experiment 1 were replicated for the inclusion of learning-relevant choices, whereas irrelevant choices were not found to significantly impact scores of transfer and external regulation. Interestingly, all students with a choice reported a lower intrinsic load, although the complexity of the learning tasks was kept constant. Highlights: Two types of feigned choice (learning-relevant and -irrelevant) were examined. Both types of choice can increase learning, autonomy and intrinsic motivation. Feigned choices also decrease a perception of external regulation and difficulty. Autonomy, but not intrinsic motivation, mediates the effect of choice on learning.